Формирование заданий для критического мышления на уроке физики - Сандибаева Н. А. Назира Абдикадировна; Склярова Е. А. Елена Александровна; Карымбай А. Н.; Токтаугалиева С. Т. (2020, 2020)
Заглавие с экрана